The effect of scanline direction and extent of rock exposure on assessment of geometrical properties of discontinuities in rock mass. (May 2019) - Ali, W; Abdullah, R A; Rehman, H; Junaid, M
Abstract: In this study, the borehole coring method and discontinuity scanline survey method are used to characterize the rock mass for the engineering design of underground structures at a dam site. Scanline survey is conducted on rock exposures in an exploratory adit. Cores from a borehole drilled near to the exploratory adit are also examined. The purpose of this study is to highlight the merits and demerits and the capacity of each method to characterize the geometrical properties of discontinuities. It is observed in the study area that the discontinuity scanline survey being conducted on large exposures, provides good results in estimating the orientation, trace length, roughness and interconnectivity of discontinuities. However, the direction of scanline introduces bias in results, because discontinuities parallel to the scanline line are not considered. The borehole method provided a good reflection of the bed rock; however, it presents a very rough estimate of geometrical properties of discontinuities. Moreover, estimation of areal extent of discontinuity plane is not covered by both the methods. However, engineering judgement by experienced engineering geologists can help in taking an informed guess.